THE ECONOMIC MECHANISM FOR ENSURING THE INNOVATIVE DEVELOPMENT OF AVIATION ENTERPRISES IN A COMPETITIVE ENVIRONMENT - ІVANETS, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the characteristics of the economic mechanism that ensures the innovative development of aviation enterprises in a competitive environment. The study's relevance is justified by the necessity for aviation enterprises to enhance their economic potential amid rising competition and the crisis in the Ukrainian market. The research employs general scientific methods, including analysis (to identify the research problem), synthesis (to formalize the economic mechanism for ensuring innovative development), generalization (to highlight conclusions), comparison (to identify trends in scientific research on the topic), and description (to present the results).The purpose of the article is to substantiate modern aspects of forming the economic mechanism for ensuring the innovative development of aviation enterprises, considering the intensification of competitive conditions.The study finds that industrial enterprises have slightly reduced their expenditures on innovation, a consequence of the challenges faced by Ukrainian aviation enterprises during wartime. It is proposed to consider innovative development as a process of transforming external competitive pressures into the internal growth potential of an enterprise. It is noted that aviation enterprises possess innovative characteristics since their activities are pioneering and highly technological. The mechanism for ensuring the innovative development of an aviation enterprise should be based on clearly defined principles. Competitive conditions necessitate the development and implementation of a mechanism for ensuring innovative development with clearly identified elements: subject, object, functions, methods, and components of innovative development. A natural outcome of implementing this mechanism is the formulation and execution of innovation strategies for aviation enterprises. Further research will focus on deepening the understanding of the significance and role of the individual elements of the economic mechanism for ensuring the innovative development of aviation enterprises proposed by the author.
Keywords: innovation; innovative development; enterprise; aviation company; competitive environment; economic mechanism